Escenarios futuros de las Food Startups en el Perú al 2040 - Gonzales Garcia, Billy Francisco (2024)
This study examines the future of Food Startups through Scenarios and Strategies towards 2040. The development of this study was based on technological foresight. The methodology was designed considering the integration of quantitative and qualitative approaches. The quantitative component was based on the use of data collection techniques, while the qualitative component was oriented towards the review and interpretation of trends and scenarios. The Delphi method in real time was employed to identify trends and Drivers in the Political-regulatory, Technological-innovation, Sociocultural, Economic-market, Environmental-sustainability, and Education-talent fields. The betting scenario was defined as "Technological and Collaborative Advancement with Moderate Financing for Food Startups in Peru. Strategic actions to achieve this scenario focus on four main areas: financing, technological innovation, collaboration and international expansion. Initially, the goal is to establish a solid base through subsidies, training and coworking spaces. Then, support needs to be intensified with tax incentives, specialized funds and acceleration programs. To continue building the scenario, the adoption of advanced technologies and the creation of patents must be encouraged. In addition, collaboration must be promoted through events, digital platforms and exchange programs. Finally, the target scenario would be built by promoting internationalization through agreements, offices abroad and "soft landing" programs.